LIBRARY PATRONAGE AMONG FACULTY AND STUDENTS OF VALLEY VIEW UNIVERSITY - Ameyaw, S. (UDS International Journal of Development, 2022)
The study examined the patronage of Walton Whaley Library of the Valley View University, Accra, Ghana. The study focused on students and faculty awareness of the library resources, the types of resources used by students and faculty, and the frequency at which users visit the university library. The stratified sampling technique was used to gather the respondents into strata – students and lecturers, before using the random sampling technique to select 513 students out of 2,172. On the side of lecturers, the entire population was used due to their small number. A well–structured questionnaire was used as the research instrument. A total of 513 copies of questionnaires were administered to the students, however, 6 copies were filled wrongly. Only 507 were used for the analysis. The quantitative data was analysed - presented in frequency and percentages with the use of the Statistical Package for Social Sciences (SPSS, version 19). The study established that the majority of the students 37.3% and lecturers 28.3% were aware of the resources in the library. Both students, 23.9%, and faculty, 28.3% patronised the library daily. The study also identified challenges like poor internet services and inadequate sitting capacity. The study recommends that management should address the issues of internet connectivity/ services in the library to enhance accessibility and effective learning. The study concluded that library management should intensify their marketing strategies to promote library resources since some users were not aware of these resources. Keywords: Academic libraries, Ghana, Paradigm, Patronage, Private Universities